Tourism of Seaside Resorts During Pandemic: Case Study of Międzyzdroje - Barbara OSÓCH; Tomasz OLECHWIR (Communications of International Proceedings, 2021)
Międzyzdroje, as one of the oldest seaside resorts on the Polish coast of the Baltic Sea, is one of the most frequently chosen areas for long-stay tourism in Poland but also has a record-high amount of 1-day tourism (1.5 million visitors to the Wolin National Park in 2019). The location, in the centre of the Pomerania Euroregion, and the extensive road network make it the heart of international tourism for tourists from all over Europe. The effects of the unusual spring-summer season are noticeable in the transformation of tourist traffic, tourist profile, and preferences such as limiting foreign trips for the benefit of increased domestic tourist traffic, and as a way of rest. The current mass tourism, for which the entire Pomerania region is known, has given way to individual tourism. In the longer term, this may result in more sustainable development of tourism – slowing down the large resorts and an enrichment of the offers related to individual stay. This observation is based on the results of three measuring tools as follows: questionnaire surveys with resort visitors, interviews with individual service providers, and road traffic registration. The aim is to identify an extremely rapidly changing set of characteristics for the current tourist and their touristic preferences. These aspects, in the social, economic, and environmental context, create the conditions for the development of a sustainable coastal tourism market near protected areas. Statistical analysis will allow, among other things, for the presentation of the similarity in the influx of tourists by voivodships with an increased incidence of Covid-19.
Keywords: Seaside Tourism; Międzyzdroje Resort; Pomerania; Tourist Traffic.